Collaborative efforts in international construction management - Abdul Rashid, Khairuddin (Procurement & Project Delivery Systems Research Unit, Kulliyyah of Architecture & Environmental, 2009)
This book, Collaborative Efforts in International Construction Management is a compilation of 35 papers and is presented in three parts: • Part 1 consisting of 7 papers for the Inaugural Conference Construction in the Muslim World. The papers contained therein review pertinent issues, problems and strategies related to the construction industries, the state of education and training and on aspects of Shari'ah compliance in construction management relevant to the countries of the Organization of the Islamic Conference (OIC) and beyond. • Part 2 consisting of 24 papers for the 5th Intemational Conference on Multi-national Joint Ventures for Construction Works. The papers contained therein examine concepts, theories, practice and discusses problems and strategies in multi-national joint ventures for construction works. • Part 3 consisting of 5 papers for the 2nd Construction Law and Economics Circle of Asia Pacific (CLECAP) conference and workshop. The papers contained therein relate to education, training and development in construction law, construction economics and in construction contract administration for experts from countries of the Asia and Pacific region.